2022
DOI: 10.3389/fonc.2022.847706
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Protein Features Predict Overall Survival and Chemotherapy Benefit in Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignant tumors with a high mortality rate worldwide and lacks effective methods for prognosis prediction. Postoperative adjuvant chemotherapy is the first-line treatment for advanced gastric cancer, but only a subgroup of patients benefits from it. Here, we used 833 formalin-fixed, paraffin-embedded resected tumor samples from patients with TNM stage II/III GC and established a proteomic subtyping workflow using 100 deep-learned features. Two proteomic subtypes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This new feature subset could be used to build a new machine learning model and its performance could be analyzed. Autoencoder neural network has been recently used extensively in medical image processing [60][61][62]. We plan to apply these networks to our dataset to see if we can come up with a better performance.…”
Section: Discussionmentioning
confidence: 99%
“…This new feature subset could be used to build a new machine learning model and its performance could be analyzed. Autoencoder neural network has been recently used extensively in medical image processing [60][61][62]. We plan to apply these networks to our dataset to see if we can come up with a better performance.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis showed patients with good revealed outcomes of the pathways that were related to DNA replication, cell cycle, and programmed cell death. Meanwhile, patients with poor outcomes are enriched in ECM-related pathways [52]. ECM constituents that characterize the matrisome of GC contexts were identified.…”
Section: Proteomics-based Validation Of Predictive and Prognostic Mar...mentioning
confidence: 99%
“…[ 1 , 2 ] According to GLOBOCAN statistics, in 2020, there were an estimated 19.3 million new cases and 10 million cancer deaths worldwide, with gastrointestinal cancers being one of the leading causes of death. [ 3 ] Currently, GC is mainly treated by surgical resection, radiotherapy, chemotherapy and targeted therapy, [ 4 , 5 ] but for metastatic gastric cancer patients, surgery is difficult to eradicate, and chemotherapeutic drugs not only have strong toxicity and side effects, but also lead to drug resistance in long-term use, [ 6 , 7 ] therefore, the development of new drugs with low side effects and anticancer effects is of great clinical significance. Studies have shown that some natural Chinese medicinal ingredients show unique advantages in anticancer, which can not only alleviate the clinical problems of strong side effects of chemotherapeutic drugs and drug resistance, but also enhance the patient own immune system, play an anti-tumor activity, thus improving the patient quality of life.…”
Section: Introductionmentioning
confidence: 99%